Antimicrobial Activity of Some Trigonella Species - Rakhee Shyam Dangi; Dasharath Oulkar; Prashant Dhakephalkar; Sanjay Kumar Singh; Kaushik Banerjee; Dattatray Naik; Shubhada Tamhankar; Suryaprakasa Rao (International Journal of Phytomedicine, 2016)
The genus Trigonella includes many medicinal and aromatic plant species used in traditional as well as veterinary medicines for different diseases, alone or in combination with other remedies. The crude methanol extracts of 15 Trigonella species were assayed for antimicrobial activity against four medicinally important multidrug resistant clinical isolates, five plant pathogenic bacteria and five fungi. Three species showed a broad spectrum of antibacterial activity inhibiting all the test bacteria. Acidified ethanolic extract of the most promising species, T. suavissima was purified by column chromatography. Characterization of a partially purified ethyl acetate fraction by LC/ESI/MS showed the presence of 7’4’ dihydroxy flavone and (2E)-3-{5-[4-(Ethoxycarbonyl)phenyl]furan-2-yl}prop-2-enoate) Three species showed strong antifungal activity against Aspergillus niger and Fusarium solani. The saponin extract of T. spicata showed a selective activity against A. niger and the sapogenin extract against F. solani. A polyhydroxylated alkaloid was isolated from the sapogenin extract of T. spicata using chromatographic techniques with structural characterization done by LC/ESI/MS, 13C and 1H NMR. The study reveals that Trigonella species are potential sources of natural compounds that may act as antimicrobial agents. It represents the most extensive survey of antimicrobial activity in Trigonella done to date.